Can Select Macroeconomic Variables Explain Long-Run Price Movements of Indian Stock Indices? - Bhuvaneshwari, D.; Ramya, K. (Indian Journal of Research in Capital Markets, 2018)
This study was an attempt to find the cointegration and causality among select macroeconomic variables namely foreign direct investment (FDI), exports, and imports and select stock indices of India like Nifty 50, Nifty FMCG, and Nifty Pharma over the period from January 2001 - December 2015. Nifty 50 and sectoral stock indices were considered as dependent variables, and select macroeconomic variables were considered as independent variables. In this study, appropriate econometric tools such as Augmented Dickey-Fuller (ADF) unit root test, Phillips - Perron (PP) unit root test, Karl Pearson's correlation coefficient, Johansen's cointegration test, vector error correction model (VECM), Granger causality test, variance decomposition index, and impulse response function were applied to analyse the linkages between select time series data. From the analysis, it was found that all the study variables were cointegrated and it was determined that select macroeconomic variables had the ability to correct the disequilibrium in the price movements of select stock indices. Granger causality test resulted in unidirectional causality between the study variables. Furthermore, it was found that sectoral stock indices responded and fluctuated with shocks to FDI, exports, and imports at a certain level of variation.